Tool support for the comprehensive modeling of quality information within business process models - Heinrich, Robert; Kappe, Alexander; Paech, Barbara (Enterprise Modelling and Information Systems Architectures (EMISA 2011), 2011)
Business process modeling is commonly used to document information about structure and behavior of a business process. However, current business process modeling notations do not support well the expression of quality information relating to business processes. Organizations are interested in the capturing of quality information for quality improvement of business processes and supporting IT systems. We are developing an approach to capture quality information comprehensively within business process models. In contrast to existing approaches, our notation allows the capturing of a broad range of quality characteristics as well as detailed attributes and measures. The approach is implemented as an extension of a CASE tool. Moreover, we discuss lessons learned from the application of the approach to a business process from practice.
Gesehen am 12.06.2020